Pre-treatment neutrophil to lymphocyte ratio predicts the chemoradiotherapy outcome and survival in patients with oral squamous cell carcinoma: a retrospective study. Issue 1 (December 2016) - Nakashima, Hikaru; Matsuoka, Yuichiro; Yoshida, Ryoji; Nagata, Masashi; Hirosue, Akiyuki; Kawahara, Kenta; Sakata, Junki; Arita, Hidetaka; Hiraki, Akimitsu; Nakayama, Hideki
Abstract Background The Neutrophil to lymphocyte ratio (NLR) has prognostic value in patients with a variety of cancers. However, its prognostic significance in oral squamous cell carcinoma (OSCC) patients has not been fully explored. The purpose of this study was to determine the clinical significance of NLR in patients with OSCC. Methods OSCC patients who underwent surgery following 5-fluorouracil (5-FU)-based chemoradiotherapy were enrolled in this study. The associations between the NLR status and various clinicopathological features were examined, and the effects of the NLR on the prognosis were evaluated. Analysis of circulating interleukin-6 (IL-6) was carried out and correlation with NLR and C-reactive protein concentration (CRP) was examined. Results An elevated NLR was significantly correlated with advanced T-stage and poor response to chemoradiotherapy. Moreover, a Cox regression analysis based on the disease-free survival (DFS) revealed the NLR status (hazard ratio, 2.013;P  = 0.041) and pathological response to chemoradiotherapy (hazard ratio, 0.226;P  = 0.001) to be significant prognostic factors in OSCC patients. Furthermore, circulating IL-6 was found to correlate with NLR and CRP. Conclusion The NLR is a potential biomarker for predicting the clinical response to 5-FU-based chemoradiotherapy and the survival in OSCC patients, and the systemic inflammatory response may be potential target for improving patient's prognosis.